Distribution and ecological aspects of Anolis (Squamata, Dactyloidae) on the main campus of the Universidad Autónoma de Santo Domingo, Santo Domingo, Dominican Republic - Joel Andrés Rojas-González; Pedro Julio Araujo-Calzado; Enrique De Jesús Frías-Victoriano; Nisia Nathaly Rosa-Delgado; Luchy Rosso-Muñoz (Check List, 2020)
We document four species of Anolis from the main campus of Universidad Autónoma de Santo Domingo: Anolis distichus (Cope, 1891), A. cybotes (Cope, 1862), A. porcatus Gray, 1840 and A. sagrei Duméril & Bibron, 1837. Anolis distichus was the most abundant species, with 176 individuals, followed by A. cybotes with 26, A. porcatus with 13, and A. sagrei with 2 individuals. We include details on the distribution and some ecological aspects of these species.